Experimental Insights Into the Threshold of Motion in Alluvial Channels: Sediment Supply and Streambed State. Issue 12 (4th December 2020) - Hassan, Marwan A.; Saletti, Matteo; Johnson, Joel P. L.; Ferrer‐Boix, Carles; Venditti, Jeremy G.; Church, Michael
Abstract: Flume experiments were conducted to understand the role of episodic sediment supply on the threshold of motion, streambed state, and stability in gravel bed channels. We demonstrate the importance of bed surface evolution on grain entrainment and hence channel stability. The grain‐size distribution (GSD) of the bed surface coarsened quickly under no feed conditions to develop an armored surface. Armor continued to experience particle exchange but remained intact throughout the experiment, and was relatively insensitive to subsequent sediment supply pulses. Bed surface structures (coarse‐grain clusters, stone cells, and imbrication) developed during the experiments and continued to respond dynamically to sediment pulses. Thresholds of motion estimated by various methods increased during the experiment and fluctuated in response to changes in sediment supply, though they were poorly predicted either by surface grain‐size changes or by surface structure. This reinforces the idea that the threshold for motion is not constant in poorly sorted gravel‐bed streams, and it confirms that the critical Shields number in transport models represents a bed state parameter, not a grain mobility number. Changes are controlled by a variety of factors including sediment supply regime, the degree of bed structuring, and the history of bed evolution. Our results highlight the importance of sediment supply regime as a control on bed surface evolution and the channel stabilizing function played by surface structures. Key Points: Despite constant flow and little change of surface grain size, critical shear stress changed in response to bed surface state Bed surface structures increased the shear stress required to entrain sediment The Shields Number is a bed state parameter